2008
DOI: 10.1002/eqe.869
|View full text |Cite
|
Sign up to set email alerts
|

Incremental dynamic analysis with consideration of modeling uncertainties

Abstract: SUMMARYIncremental dynamic analysis (IDA) has been extended by introducing a set of structural models in addition to the set of ground motion records which is employed in IDA analysis in order to capture record-to-record variability. The set of structural models reflects epistemic (modeling) uncertainties, and is determined by utilizing the latin hypercube sampling (LHS) method. The effects of both aleatory and epistemic uncertainty on seismic response parameters are therefore considered in extended IDA analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
165
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(182 citation statements)
references
References 25 publications
(35 reference statements)
9
165
0
8
Order By: Relevance
“…Compared to some other studies in this area [24,25], this number of realizations seems to be sufficient.…”
Section: Parameters Of the Structural Modelmentioning
confidence: 73%
See 1 more Smart Citation
“…Compared to some other studies in this area [24,25], this number of realizations seems to be sufficient.…”
Section: Parameters Of the Structural Modelmentioning
confidence: 73%
“…This technique uses a constrained sampling scheme instead of random sampling utilized by direct Monte Carlo method, and consequently will need significantly fewer simulations to cover desired probability space [24,25]. This property can become very helpful to decrease the high computational costs usually associated with uncertainty studies.…”
Section: Description Of Damages In a Probablistic Frameworkmentioning
confidence: 99%
“…As such, the number of realisations was chosen here to be 40. This number was selected based on the parametric study by [13] who noted that 20 appeared to be a reasonable value. Also of note are the correlations assumed between different RVs, which were assumed to be independent and uncorrelated for simplicity of analysis.…”
Section: Analysis Of Model Realisationsmentioning
confidence: 99%
“…38,39]. Because of the likely dependence on model configuration it is suggested that correlation between EDP|IM epistemic uncertainties is also handled in a non-parametric logic tree format.…”
Section: Correlations In Epistemic Uncertaintiesmentioning
confidence: 99%